Perbedaan Hasil Belajar Model Pembelajaran Problem Posing dan Question Student Have pada Kelas IX - Riski Nur Istiqomah Dinnullah; Sis Kanti; Yuniar Ika Putri Pranyata (Universitas Bhinneka PGRI, 2021)
Whether or not there are differences in learning outcomes using the Problem Posing and Question Student Have (QSH) learning models for class IX students at MTs Nurul Mubtadiin is the goal of this study. The quantitative method used in this research is a quasi- experimental type. All students of class IX MTs Nurul Mubtadiin for the academic year 2020/2021 were used as the population in this study. Purposive sampling method was used for sampling and then the experimental class 1 was selected, namely class IX-1 and class IX- 2 was selected as experimental class 2 in this study. Researchers used tests to obtain data. The test goes through the instrument test phase which consists of a validity test and a reliability test before being used. Normality test, homogeneity test, and hypothesis testing (Independent Sample T-Test) are the stages that are passed in analyzing the data in this study. It is known that there are differences in learning outcomes with the treatment of the Problem Posing and Question Student Have (QSH) models for class IX students at MTs Nurul Mubtadiin on the results of the study. In the hypothesis test conducted with the (Independent Sample T-Test) when testing the hypothesis by obtaining a significance value, which shows the number. In the experimental class 1 and 2, it was found that there was a difference in the average value. The experimental class 1 obtained an average score while the average value was obtained by the experimental class 2. So that it can be said, when compared to the Question Student Have (QSH) model, the Problem Posing model is a better model.